Analisis Pengaruh Store Atmosphere dan Brand Image Terhadap Keputusan Pembelian Stuja Coffee Jakarta - Mario Zyco Halomoan; Siti Nurjanah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research was conducted to analyze the factors that most influence the purchasing decision at the Stuja coffee shop. The factors that will be studied are store atmosphere and brand image. These factors are considered to have contributed significantly to consumer purchasing decisions. Analysis techniques used in this research is a quantitative. This study uses samples data from 200 respondents who have purchased coffee at Stuja Kopi Jakarta. The results of this study show that the factor of store atmosphere and brand image is the most influencing factor in purchasing decisions. The discovery of easy information can make consumers more familiar with the coffee products offered so that the decision to buy coffee products at Stuja Kopi Jakarta is getting bigger.